2016
DOI: 10.1152/physrev.00014.2015
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: Metabolism, Molecular Mechanism of Action, and Pleiotropic Effects

Abstract: , [1,25(OH) 2 D 3 ] is the hormonally active form of vitamin D. The genomic mechanism of 1,25(OH) 2 D 3 action involves the direct binding of the 1,25(OH) 2 D 3 activated vitamin D receptor/retinoic X receptor (VDR/RXR) heterodimeric complex to specific DNA sequences. Numerous VDR co-regulatory proteins have been identified, and genome-wide studies have shown that the actions of 1,25(OH) 2 D 3 involve regulation of gene activity at a range of locations many kilobases from the transcription start site. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
1,234
1
73

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,473 publications
(1,453 citation statements)
references
References 538 publications
14
1,234
1
73
Order By: Relevance
“…Net effects include strong suppression of cancer cell proliferation and differentiation (30). More recent evidence suggests, however, that vitamin D can also exert fast, non-genomic actions (31,32). …”
Section: Vitamin Dmentioning
confidence: 99%
“…Net effects include strong suppression of cancer cell proliferation and differentiation (30). More recent evidence suggests, however, that vitamin D can also exert fast, non-genomic actions (31,32). …”
Section: Vitamin Dmentioning
confidence: 99%
“…[3][4][5] Vitamin D 3 , when converted in the kidney to calcitriol, acts as a potent steroid hormone on various organs, such as the intestine, bone, kidney, and parathyroid, primarily to promote homeostasis of blood calcium levels. 6,7 As a result of adverse events related to the deleterious effects of hypercalcemia, calcitriol analogs, such as paricalcitol, have been developed to circumvent this problem. 8,9 A number of clinical trials have demonstrated the efficacy of paricalcitol in decreasing proteinuria [10][11][12] and excessive parathyroid hormone (PTH) due to secondary hyperparathyroidism (SHPT) associated with chronic kidney disease [13][14][15] or following kidney transplant.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of vitamin D is photosynthesized in the skin by the action of solar UVB radiation was 7-dehydrocholesterol convert to Vitamin D3 [7]. The humans need continuous glucose level in their blood, which allows the brain to work even with minimum function.…”
Section: Introductionmentioning
confidence: 99%